2015
DOI: 10.1038/eye.2015.11
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal analysis of age-related changes in intraocular pressure in South Korea

Abstract: Purpose To assess the changes in intraocular pressure (IOP) with age in South Korea Methods Subjects aged 20-79 who had been receiving health examinations at a university hospital were enrolled. They completed physical and ophthalmic examinations. Subjects with ocular disease that could possibly affect their IOP were excluded. The relationships between IOP and age, blood pressure, heart rate, body mass index, blood chemistry, and electrolyte were analyzed using a linear mixed model. Results Of the 33 712 subje… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
28
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 25 publications
2
28
1
Order By: Relevance
“…In the existing literature, longitudinal studies on age-related IOP changes have mainly been based on Caucasian and African populations, and reported an overall increasing trend of IOP with age. 10 A longitudinal Korean study reported an average of −0.065 mmHg change of IOP per year based on a large cohort, following up for 8 years. Nomura et al reported that IOP increased significantly with aging in both males and females in an 8 year follow-up, which is consistent with our findings.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In the existing literature, longitudinal studies on age-related IOP changes have mainly been based on Caucasian and African populations, and reported an overall increasing trend of IOP with age. 10 A longitudinal Korean study reported an average of −0.065 mmHg change of IOP per year based on a large cohort, following up for 8 years. Nomura et al reported that IOP increased significantly with aging in both males and females in an 8 year follow-up, which is consistent with our findings.…”
Section: Discussionmentioning
confidence: 99%
“…2 Intraocular pressure (IOP) had been widely acknowledged as the most important modifiable risk factor for the development of glaucoma, but the reported age-related IOP change remains inconsistent. [7][8][9][10] Whether this is due to true aging effect or cohort effect is still in contention. [7][8][9][10] Whether this is due to true aging effect or cohort effect is still in contention.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…7 There are differences in ethnic groups, and both positive and negative relationships between increased age and IOP have been described. 8,9 Although the outflow seems to decrease with age, the production of AH may also decrease. 10 …”
mentioning
confidence: 99%